In Utero Chlordecone Exposure and Thyroid, Metabolic, and Sex-Steroid Hormones at the Age of Seven Years: A Study From the TIMOUN Mother-Child Cohort in Guadeloupe - Ayhan, Gülen; Rouget, Florence; Giton, Frank; Costet, Nathalie; Michineau, Léah; Monfort, Christine; Thomé, Jean-Pierre; Kadhel, Philippe; Cordier, Sylvaine; Oliva, Alejandro; Multigner, Luc (Frontiers in Endocrinology, 2021)
Background Chlordecone is an endocrine-disrupting chemical with well recognized estrogenic and progestagenic properties. This organochlorine insecticide was extensively used in the French West Indies from 1973 to 1993 to control the banana root borer. Due to its poor degradation in the environment, permanently polluted soil is responsible for the current contamination of the food chain and human beings. We aimed to examine the relationship of in utero exposure to chlordecone and thyroid (thyroid stimulating hormone [TSH], free tri-iodothyronine [FT3], free thyroxine [FT4], metabolic (insulin growth-factor 1, leptin, adiponectin), and sex-steroid (dehydroepiandrosterone [DHEA], total testosterone [TT], dihydrotestosterone [DHT], estradiol [E2]) hormone levels in children at the age of seven years who participated in TIMOUN, an ongoing birth cohort in Guadeloupe. Methods Chlordecone concentrations were measured in cord-blood at delivery. Thyroid, metabolic, and sex-steroid hormone levels were determined in the blood of children at seven years of age. Associations between in utero chlordecone exposure and hormone levels at seven years of age were assessed by multiple linear or logistic regression, controlling for confounding factors. Results Among the study population (210 boys and 228 girls), chlordecone and hormone measurements were available for 124 boys and 161 girls. We found the third quartile of in utero chlordecone exposure relative to the lowest quartile to be associated with elevated TSH levels in girls and elevated DHEA, TT, and DHT levels in both sexes. Complementary non-linear analysis (spline regression) confirmed a significant non-linear trend for TSH in girls and DHEA and DHT in boys. Conclusion In utero chlordecone exposure was associated with elevated levels of selected thyroid (TSH) and sex-steroid (DHEA, TT, and DHT) hormones at seven years in a non-monotonic dose response (inverted U) relationship. The implications for future health and reproductive function in puberty and adulthood should be determined.